大功率循环泵行星齿轮箱耦合动态特性分析 - 杨长辉; 吴灿元; 谭勇虎; 许洪斌 (Jixie chuandong)
A coupled dynamics model containing gears-shafts-bearings-housing of a high-power circulating pump planetary gearbox is built comprehensively in consideration of the time-varying mesh stiffness and gear error. The coupled modal analysis is performed for this finite element model of the gearbox.The dynamic response is solved by using mode superposition method.Then the time-frequency history of node displacement and speed of the gearbox are obtained.All results provided a theoretical foundation for dynamic characteristic optimization of a high-power circulating pump planetary gearbox transmission system.